Cambodia : Staff Report for the 2002 Article IV Consultation and Sixth Review Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines Cambodia's 2002 Article IV Consultation and Sixth Review Under the Poverty Reduction and Growth Facility (PRGF). Supported by inflows of development aid, economic activity regained vitality in 1999. The government's macroeconomic strategy, which was supported by a PRGF arrangement, yielded positive results. Economic performance in 2002 was broadly satisfactory. Real GDP is estimated to have slowed to 4 1\2 percent owing to adverse weather conditions. All end-September quantitative performance criteria and the structural performance criterion for end-October were observed. Progress in structural reforms has been broadly satisfactory, albeit with some delays.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet